Fixed Point Results for Rational Orbitally (Θ,δb)-Contractions with an Application - Zhenhua Ma; Jamshaid Ahmad; Abdullah Eqal Al-Mazrooei; Durdana Lateef (Journal of Function Spaces)
The purpose of this paper is to define a rational orbitally (Θ,δb)-contraction and prove some new results in the context of b-metric spaces. Our results extend, generalize, and unify some known results in the literature. As application of our main result, we investigate the solution of Fredholm integral inclusion. We also provide an example to substantiate the advantage and usefulness of obtained results.